2012
DOI: 10.5171/2012.622123
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention towards the Use of 3G Technology

Abstract: Nowadays, 3G technologies provide people with higher wireless bandwidth, audio and video services, as well as mobile internet access all in one mobile environment. The information technology industry needs to understand why people prefer this technology, which variables and opportunities convinced them to use it. The focus of this study is to examine the factors affecting 3G technology perception and adoption. In the theoretical framework of the study, Technology Acceptance Model (TAM) and Unified Theory of Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
3
18
1
3
Order By: Relevance
“…It means that the students' intention to use this technology is influenced by their friends, family member, lecturers, and other social surroundings. The results of this study are supported by several previous studies, that found this construct to be a major predictor of consumers' intention to use the technology (Du et al, 2012;Mardikyan et al, 2012;Ong et al, 2008;Wu et al, 2007). The construct was significant predictor in the context of Malaysia, China, Turkey, and Taiwan.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…It means that the students' intention to use this technology is influenced by their friends, family member, lecturers, and other social surroundings. The results of this study are supported by several previous studies, that found this construct to be a major predictor of consumers' intention to use the technology (Du et al, 2012;Mardikyan et al, 2012;Ong et al, 2008;Wu et al, 2007). The construct was significant predictor in the context of Malaysia, China, Turkey, and Taiwan.…”
Section: Discussionsupporting
confidence: 80%
“…Du et al (2012) found perceived price to have negative effect on the behavioral intention to use 3G technology among Chinese consumers. In addition, Ong et al (2008) and Mardikyan et al (2012) …”
Section: Perceived Expensementioning
confidence: 98%
See 2 more Smart Citations
“…In this regard, recent studies in wide-ranging research domains have adopted the UTAUT as the underlying theoretical basis. These studies have included an examination of organizational learning systems (Wong and Huang, 2011), mobile banking implementations (AbuShanab and Pearson, 2007;Zhou, 2012), 3G mobile communication (Mardikyan et al, 2012;Wu et al, 2012) and wireless communications (Anderson and Schwager, 2004). Furthermore, the UTAUT has been adopted as the theory to examine the acceptance by students of blackboard technology as indicated by Marchewka and Kostiwa (2014); Pynoo et al (2011) applied UTAUT to measure the level of acceptance and utilization of a digital learning environment by secondary school teachers, and UTAUT has been adopted as the theoretical framework to examine training in health care systems (Marshall et al, 2011).…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%